Serum cytokine profiles in Takayasu's arteritis: search for biomarkers - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2015)
Objective. Assessment of disease activity is one of the major difficulties in patients with Takayasu arteritis (TA) during follow-up. To date, no biomarker is universally accepted to be a surrogate for active disease in TA. In this study, we aimed to investigate levels of various pro-and anti-inflammatory, molecules including serum granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin (IL)-6, IL-8, IL-10, IL-18 and IL-23 in patients with TA. Methods. The study included 51 patients (age: 40.6 +/- 12.2 years, F/M: 45/6) with TA and 42 age- and sex-matched healthy controls (age: 38.1 +/- 7.4 years, FIM: 38/4). All patients fulfilled the criteria of the American College of Rheumatology (ACR). TA patients were evaluated by physician's global assessment (PGA; active/inactive) and ITAS2010 (Indian Takayasu Arteritis Clinical Activity Score) in terms of clinical activity in baseline and follow-up visits. Commercial enzyme linked immuno-sorbent assay (ELISA) kits were used for measurements of serum cytokine levels. Results. At baseline, 21(41.2%) patients were active according to PGA and 8 (15.7%) according to ITAS2010. Serum IL-6, IL-8 and IL-18 levels were significantly higher in patients with TA, whereas GM-CSF, IL-10, IL-23 levels were similar to healthy controls. IL-8 significantly decreased in the follow-up, associated with a decrease of clinical activity, whereas IL-23 level significantly increased. When assessed by ITAS2010 active patients had significantly higher IL-18 levels. Conclusion. We found significantly increased IL-6, IL-8 and IL-18 levels in patients with TA compared to healthy controls. Only IL-18 level was significantly higher in active patients assessed by ITAS2010. IL-18 was also the only cytokine in our study that correlated with CRP. These findings suggest that cytokines associated with neutrophilic, pro-inflammatory responses such as IL-6, IL-8 and IL-18 can be potential biomarkers for the assessment of disease activity in TA and warrant further studies in larger series.
Keywords: Takayasu's arteritis; biomarkers; disease activity; GIANT-CELL ARTERITIS; COLONY-STIMULATING FACTORS; DISEASE-ACTIVITY; POLYMYALGIA-RHEUMATICA; AUTOIMMUNITY; LYMPHOCYTES; DIAGNOSIS; INTERLEUKIN-18; TOCILIZUMAB; VASCULITIS